Long Term Effects of COVID-19 among RT-PCR Positive Bangladeshi Patients (Journal of Chittagong Medical College Teachers' Association, 2021)
Background: COVID-19 was an unknown disease previously. This pandemic has affected almost all countries of the world and creating a deadly experience to all. It leads to long term squeals among many affected people with consequent loss of productivity and quality of life. This entity is called long COVID syndrome. The objectives of the present study is to find out the long term sequels of COVID-19 patients.Materials and methods: This was an observational study where a total of 56 patients of COVID-19 were recruited. Demographic data and long term sequelae were recorded from these patients. All the patients were confirmed cases of COVID-19 by RT-PCR. Prior consent from the patients and ethical clearance was taken. Data were analyzed by SPSS-20.Results: Among 56 cases male was 31(55.4%) and female was 25(44.6%). Male to female ratio was 1.24:1. Age group distribution showed